What Is at Stake in the Recognition of Non-Normative Identities? - Rodríguez Ruiz, Blanca (The Age of Human Rights Journal, 2022)
The deconstruction of the binary sex-gender system that sustains modern western states demands the deconstruction of its dichotomies and their excluding effects on non-normative identities. This demands in turn that gender self-determination be recognised as a right. In Spain this right has been given constitutional status (STC 99/2019), yet it is currently not articulated in legislation. Proposals of a new legal framework have met with resistance and an ensuing need for compromise. Unless it grasps and upholds the full constitutional extent of the right to gender self-determination, however, legislation risks being born both unconstitutional and obsolete, out of pace with social demands.